The fight to resurrect Rutherford’s mana in New Zealand - Campbell, John (New Zealand Science Review, 2016)
Did I win the fight? Sadly, no. I won some battles but lost the war. To disbelieving scientists, I need to explain this statement. There have been two History of New Zealand Science Conferences, in 1983 and 2015. Apparently I am the only person who attended both. In 1983 my talk was ‘Researching the life of Earnest Rutherford’. In 2015 it was ‘The fight to resurrect Rutherford’s mana in New Zealand.’ This account gives my experiences in-between. Although a Canterbury graduate and long-serving academic, I first became interested in Rutherford by accident. Because I had an interest in marine archaeology, which was as close to the history of science as anyone got in those days, in 1977 I was invited to join a committee to set up the first Rutherford Den. That opened my eyes to the startling fact that, at that time, New Zealand could not give an accurate account of its internationally most famous son​